Surviving Stress: rediscover the awesome you - Bhatnagar, Vidhu (Delhi Education, 2011)
This book is divided into two sections- the first section deals with the lessons I learnt regarding stress management and the second is devoted to learning about the societal conditioning and rediscovering our awesomeness.